AB0566 Anti-phospholipid antibodies sero-negativization in systemic lupus erythematosus patients treated with belimumab. (12th June 2018) - Rubini, E.; Radin, M.; Cecchi, I.; Roccatello, D.; Sciascia, S.
Abstract : Background: Belimumab is a monoclonal antibody that blocks the B lymphocyte stimulator, preventing it to bind its receptor on B-lymphocyte's surface, thus avoiding B cell activation. Despite some benefits showed in murine models of anti phospholipid syndrome (APS), 1 the use of belimumab in this condition needs further investigation. Objectives: To investigate changes in the antiphospholipid antibodies (aPL) profile in Systemic Lupus Erythematosus (SLE) patients treated with belimumab. Methods: We retrospectively collected data from patients who attended the S. Giovanni Bosco Hospital, Turin, Italy. Inclusion criteria comprised: a) fulfilled ACR criteria for SLE, b) persistent aPL positivity (confirmed ≥3 occasions over a time >24 months before belimumab treatment), c) previous or ongoing belimumab therapy. Results: This retrospective study included 3 patients with diagnosis of SLE [median age 39(range 33–51), male:female 2:1]. Table 1 resumes the characteristics of patients. All 3 patients received belimumab because of SLE flares. Before the treatment, Patient#1, classified as SAPS, 2 presented a persistent triple positivity for lupus anticoagulant (LA), high-titer aCL IgG isotype (>200 GPL) and anti-β2glicoprotein I antibodies (>50 GPL) (anti-β2GPI) IgG isotype. Patient#2 was persistently positive for IgG aCL and IgM anti-β2GPI (both 20–30 GPL and MPL, respectively; cut-off >7U), and had a history of pregnancy morbidity. Patient#3, classified as SAPS, presented positivity of LA and IgG aCL (10–20 GPL). After 12 months since belimumab was started, a marked reduction of aPL was noticed, as follows. Patient#1 became negative for antiβ2GPI, while his aCL titre significantly decreased. Anti-β2GPI and aCL both turned negative in Patient#2 . After being on belimumab for one year, she planned a pregnancy and she stopped the treatment; after 8 months since suspension, IgG antiβ2GPI antibodies were detectable (cut-off >3.5 U). Patient#3 was persistently negative for aCL while being on belimumab. When he discontinued the therapy, IgG aCL antibodies returned positive. Figure 1 illustrates aPL titres of the 3 patients in relationship with belimumab therapy. Conclusions: Despite its limitations, this pilot study is the first report of aPL negativization after starting therapy with belimumab. The clinical relevance of these findings should be investigated in prospective multicenter studies. References: [1] Khattri S, Zandman-Goddard G, Peeva E. B-cell directed therapies in antiphospholipid antibody syndrome–new directions based on murine and human data. Autoimmun Rev2012;11:717–22. [2] Miyakis S, Lockshin MD, Atsumi T, et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost2006;4:295–306. Disclosure of Interest: None declared